The symbolic significance of models of Algerian traditional customs in dress, jewelry, and adornment, and their background in ancient history - fares, daas (The Algerian Historical Journal, 2026)
This article aims to shed light on some models of dress and adornment in the contemporary Algerian cultural heritage, and we try to trace its ancient historical roots, and monitor its various symbolic dimensions and connotations, using the tools of anthropology, by which we mean: description, analysis, and comparison. The study finally concluded that dress and adornment, such as: the Tuareg belt, the Amazigh khalala, shaving, the Kabylie barnos, and tattoos, are among the basic pillars of the contemporary Algerian cultural heritage, and this was confirmed by ancient material sources and Greek and Latin literary texts that pertained to the ancient history of Algeria.